DIGITAL IMPLICATIONS IN THE SUCCESS OF PROSTHETIC RESTORATIONS - Crețu Cosmin – Ionuț; Tibeică Andreea; Curcă Răzvan; Agop-Forna Doriana; Orghidan Cristian; Ulman Cosmin; Iacob Andrei; Norina Forna (Romanian Journal of Oral Rehabilitation)
The advent of digital technologies in dentistry has revolutionized prosthetic restoration procedures, offering enhanced accuracy, efficiency, and patient satisfaction. This meta-analysis evaluates the impact of digital workflows, computer-aided design and manufacturing (CAD/CAM) systems, and 3D printing on the success rates of prosthetic restorations. Through a comprehensive review of peer-reviewed literature, the study identifies critical technological factors influencing clinical outcomes, patient-reported satisfaction, and procedural efficiency. The findings highlight the superiority of digital approaches over conventional techniques in terms of precision, fit, and reduced chairside time. CAD/CAM systems enable the production of highly precise restorations with significantly improved marginal and internal fit, leading to better clinical success rates. The shift from traditional impression-taking methods to intraoral scanners results in higher patient satisfaction due to improved comfort and shorter treatment times. Moreover, 3D printing facilitates rapid prototyping and on-demand production of dental prostheses, enabling faster turnarounds and cost-effective customization. The study also explores procedural efficiency, noting that digital workflows significantly reduce chairside time and treatment duration. This reduction enhances clinical efficiency and patient throughput, allowing dental clinics to serve more patients while maintaining high-quality standards. The pooled success rate of digital prosthetic restorations was found to be 92%, substantially higher than that of conventional methods.